2019
DOI: 10.35940/ijitee.b7668.129219
|View full text |Cite
|
Sign up to set email alerts
|

Simulation and Experimental Substantiation of Beam Deflection under Guided End Conditions

S. Gurumoorthy*,
L.Bhaskara Rao

Abstract: This paper studies the nonlinear deflection characteristics of a rectangular cross sectional beam with guided support conditions. In this study two different end conditions namely guided – guided and guided – simply supported have been examined. Beams made with two dissimilar materials for instance, aluminum and steel have been considered for this study. Different loading conditions namely point load and the amalgamation of uniformly distributed load and point load have been taken into account in this study. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…In many engineering systems, beams are common structural elements. A bunch of beam problems have been investigated recentlysee, e.g, (Ecsedi and Gönczi, 2015;Gurumoorthy and Rao, 2019;. When a straight beam is loaded with an axially compressive force, it exhibits minor deformations until it reaches a critical condition known as buckling at the critical load value.…”
Section: Introductionmentioning
confidence: 99%
“…In many engineering systems, beams are common structural elements. A bunch of beam problems have been investigated recentlysee, e.g, (Ecsedi and Gönczi, 2015;Gurumoorthy and Rao, 2019;. When a straight beam is loaded with an axially compressive force, it exhibits minor deformations until it reaches a critical condition known as buckling at the critical load value.…”
Section: Introductionmentioning
confidence: 99%
“…The design of various steel structures used in different industrial applications is a difficult task for design engineers. This difficulty stems from multiple considerations like applied load, variation in span, different crosssectional members, the material used, use of stiffeners and reinforcement, and applied boundary conditions (Gurumoorthy and Rao 2019). It is very important to study the effect of multiple considerations on a beam's deflection to verify the beam strength according to applied load and application.…”
Section: Introductionmentioning
confidence: 99%
“…The beam has to be designed so as to withstand the applied load together with any other relevant parameters and considerations specific to the industrial applications. In this regard, different loads such as UDL (Gurumoorthy Gurumoorthy and Rao (2019) investigated experimentally the nonlinear deflection characteristics of a rectangular cross-sectional beam for point load and uniformly distributed load. They found that sectional properties, material, loading, and boundary conditions greatly influence the beam behavior.…”
Section: Introductionmentioning
confidence: 99%